The Tourism as A Potential Sector in Serang - Lia Uzliawati; Widya Nur Bhakti Pertiwi (Journal of Applied Business, Taxation and Economics Research, 2021)
Serang has the potential for tourism objects to continue to be developed with a tourism-based development pattern that can contribute to the economic growth of Serang. The purpose of this study was to find out which urban areas have tourism potential as a leading sector in Serang. The focus of this research is located in the district of Kasemen, Serang. The analytical method used is SWOT analyis. The results of the study show that there are several villages that have the potential to be the leading sector in the Kasemen District.